The Cooperation in Reduction of the Social Exclusion of Youth - Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper focuses on problems of the social exclusion of young people and its resolution questions. The problems in society caused by socio-economic factors significantly influence the life of youth. The objective of this paper: by considering the analysis of theoretical findings, to evaluate the cooperational experience in pedagogical practice, how to solve problems of youth social exclusion in Liepaja. The research implements sociological and educationally psychological literature analysis, in order to create comprehension of the causes of social exclusion of young people, contraversies of life quality and personal self-improvement opportunities. The author realizes analysis of five expert interview results, in order to explore the youth concerns and opportunities of reduction of youth social exclusion, as well as mechanisms and instruments of existing cooperatioon in Liepaja municipality.